Panu - Aho, Juhani, 1861-1921 (Salt Lake City, UT : Project Gutenberg, 2004)
"Panu" by Juhani Aho is a novel written during the early 20th century. The narrative explores the tensions between pagan traditions and Christianity in a remote Finnish setting, featuring characters such as Panu, a powerful seer, and his various interactions with different social groups, including settlers and native inhabitants. The book delves into themes of belief, identity, and cultural conflict, providing a rich backdrop of life in the wilderness. At the start of "Panu," we are introduced to the landscape around Kontojärvi, where a small church and village coexist near a tumultuous river. The narrative reveals the history of this place, describing its inhabitants and their rituals, with a focus on the conflict that arises between the local pagan traditions and the new Christian faith. Panu is portrayed as a significant figure, a wielder of ancient knowledge who navigates the struggles of both the Savolaiset and Karjalaiset people, while the story also hints at impending changes brought about by outside forces, including the influence of the church and government. The opening establishes a vivid sense of time and place, setting the stage for the unfolding drama of cultural clash and personal destiny. (This is an automatically generated summary.)
Release date is 2004-10-25
Produced by Tapio Riikonen
Keywords: Finland -- History -- To 1523 -- Fiction